Expression of Identity in Tattoos of Symbols of Different Cultures - Černikovaitė, Miglė Eleonora; Mitkutė, Meda (Information & Media, 2023)
The construction and expression of identity in the context of globalization and digitalisation is a problematic task in the modern world, where the processes of identity self-creation allow oneself to choose from many different options. The problem of this work is the communication of identity of tattooed people through tattoos of symbols of different cultures. The aim of the work is to examine the aspects of the identity communication of tattooed persons. Semi-structured interview and qualitative analysis methods are used to implement the aim and objectives of the work.The obtained results reveal that the processes of identity construction and expression use the methods of creation and interpretation of semantic connections, reflexive individualization, multi-layered coding of symbols, incorporating elements of different cultures into the identity project, which include symbolic, philosophical, spiritual, aesthetic and mythological assimilation prisms. The intervention of the Other in projecting personal identity becomes the identity insertion, and tactile senses, sight and hearing help to assimilate different cultures through different existing life articulations. In the context of social interaction, virtual identity is transferred into material forms of expression of identity and, with the help of the body as a media, extends identity beyond technology and deletes boundaries between it.
Keywords: identity; symbols of different cultures; tattoos; the body as a medium; social interactions; digitization